The Essential Guide to Open Source Flash Development - Chris Allen, Wade Arnold, Aral Balkan, Nicolas Cannasse, John Grden, Moses Gunesch, Marc Hughes, R. Jon MacDonald, Andy Zupko (Springer, 2017)
398 p.